2021
DOI: 10.21541/apjes.779495
|View full text |Cite
|
Sign up to set email alerts
|

Channel in Multiple Transmitter Visible Light Communication

Abstract: Aydınlatma için kullanılan ışık kaynaklarını veri iletiminde kullanma fikrine dayanan Görünür Işık Haberleşmesinin (Visible Light Communication, VLC) geleceğin haberleşme teknolojileri arasında yer alması beklenmektedir. Ancak güvenilir iletişim için çokyollu yapıya sahip olduğu bilinen bina içi VLC kanallarının bilinmesi ve kestirilmesi önemlidir. Bu nedenle olası kanal karakteristiklerini incelemek amacıyla, çalışmada farklı boyutlarda çeşitli düzende yerleştirilmiş çoklu vericili odalar ele alınmıştır. Mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Ten thousand rays were generated in each simulation, with the assumption that there was no diversity or multiplexing. Channels that occurred in various conditions were investigated, and it was concluded that, although there was an infinite number of reflections theoretically, the NLOS paths caused light movements in CFRs, which were insignificant compared with the fluctuations due to the LOS paths in the multisource case, as also proven in Kimyacı and Çürük [18]. Therefore, all reflections were ignored while analyzing the channels of VLC with multisource in this study.…”
Section: Analysis Of Indoor Vlc Channelsmentioning
confidence: 91%
See 1 more Smart Citation
“…Ten thousand rays were generated in each simulation, with the assumption that there was no diversity or multiplexing. Channels that occurred in various conditions were investigated, and it was concluded that, although there was an infinite number of reflections theoretically, the NLOS paths caused light movements in CFRs, which were insignificant compared with the fluctuations due to the LOS paths in the multisource case, as also proven in Kimyacı and Çürük [18]. Therefore, all reflections were ignored while analyzing the channels of VLC with multisource in this study.…”
Section: Analysis Of Indoor Vlc Channelsmentioning
confidence: 91%
“…Notably, the emitted power of point sources is found by multiplying the received powers by reflecting coefficients of the surfaces. Then, although there exist an infinite number of reflections, emitted power will be negligible after the first few ones [18].…”
Section: Indoor Vlc Channelsmentioning
confidence: 99%
“…Specifically, IoT (Internet of Things) technology which is one of the backbones of industrial systems has been recently combined to VLC systems to provide energy efficiency [19]. Moreover, channel modelling and indoor positioning are very attractive issues for VLC systems such as RF systems (20)(21)(22)(23).…”
mentioning
confidence: 99%